2019
DOI: 10.1111/jog.14099
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the desire to have children and engage in sexual activity after trachelectomy among young Japanese women with early‐stage cervical cancer

Abstract: Aim: To evaluate how the desire to have children and engage in sexual activity change after trachelectomy in Japanese women with early-stage cervical cancer who strongly desired to have children before surgery. Methods: Desire to have children, coital pain, fear of sexual intercourse, sexual activity frequency and libido were assessed in cervical cancer patients who received follow-up after trachelectomy. An anonymous questionnaire survey was conducted via informed consent. Results: Of the 151 patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…4,5,7 In addition, sexual dysfunction may also negatively affect the relationship between CC patients and their spouses, leading to emotional alienation and marital problems. 4,6,8,9 In previous studies, the short-term sexual function of CC survivors has been extensively discussed, while further attention needs to be paid to long-term follow-up of those survivors. The present study aimed to evaluate the long-term sexual function of CC survivors after cancer therapy (follow-up time, 13-138 months), and to investigate the possible effects of multiple treatment modalities and demographic variables on the sexual function of CC survivors using the validated short form of Pelvic Organ Prolapse/ Urinary Incontinence Sexual Questionnaire (PISQ-12).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,5,7 In addition, sexual dysfunction may also negatively affect the relationship between CC patients and their spouses, leading to emotional alienation and marital problems. 4,6,8,9 In previous studies, the short-term sexual function of CC survivors has been extensively discussed, while further attention needs to be paid to long-term follow-up of those survivors. The present study aimed to evaluate the long-term sexual function of CC survivors after cancer therapy (follow-up time, 13-138 months), and to investigate the possible effects of multiple treatment modalities and demographic variables on the sexual function of CC survivors using the validated short form of Pelvic Organ Prolapse/ Urinary Incontinence Sexual Questionnaire (PISQ-12).…”
Section: Introductionmentioning
confidence: 99%
“…At present, surgery is the main therapeutic approach for early‐stage CC, and adjuvant radiotherapy and chemotherapy are used according to patients' clinical conditions. Patients may receive multiple treatment modalities, accompanied with long‐term influences on sexual function, and numerous studies have shown that there is a correlation between CC treatment and changes in sexual function 4–6 . A large number of studies have reported that CC survivors mainly suffer from sexual discomfort, vaginal shortening, decreased vaginal elasticity, pelvic nerve damage, vaginal dryness, dyspareunia, insertion pain, vaginal bleeding, and decreased sexual interest compared with healthy controls 4,5,7 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations